Intraoperative complications in kidney tumor surgery: critical grading for the European Association of Urology intraoperative adverse incident classification - Nisen Harry; Erkkilä Kaisa; Ettala Otto; Ronkainen Hanna; Isotalo Taina; Nykopp Timo; Seikkula Heikki; Seppänen Marjo; Tramberg Margus; Palmberg Christian; Kilponen Ansa; Pogodin-Hannolainen Dimitri; et al. (Taylor & Francis Ltd, 2022)
Introduction
The European Association of Urology committee in 2020 suggested a new classification, intraoperative adverse incident classification (EAUiaiC), to grade intraoperative adverse events (IAE) in urology.
Aims
We applied and validated EAUiaiC, for kidney tumor surgery.
Patients and methods
A retrospective multicenter study was conducted based on chart review. The study group comprised 749 radical nephrectomies (RN) and 531 partial nephrectomies (PN) performed in 12 hospitals in Finland during 2016–2017. All IAEs were centrally graded for EAUiaiC. The classification was adapted to kidney tumor surgery by the inclusion of global bleeding as a transfusion of ≥3 units of blood (Grade 2) or as ≥5 units (Grade 3), and also by the exclusion of preemptive conversions.
Results
A total of 110 IAEs were recorded in 13.8% of patients undergoing RN, and 40 IAEs in 6.4% of patients with PN. Overall, bleeding injuries in major vessels, unspecified origin and parenchymal organs accounted for 29.3, 24.0, and 16.0% of all IEAs, respectively. Bowel (n = 10) and ureter (n = 3) injuries were rare. There was no intraoperative mortality. IAEs were associated with increased tumor size, tumor extent, age, comorbidity scores, surgical approach and indication, postoperative Clavien–Dindo (CD) complications and longer stay in hospital. 48% of conversions were reactive with more CD-complications after reactive than preemptive conversion (43 vs. 25%).
Conclusions
The associations between IAEs and preoperative variables and postoperative outcome indicate good construct validity for EAUiaiC. Bleeding is the most important IAE in kidney tumor surgery and the inclusion of transfusions could provide increased objectivity.